Repentance and rebirth at the end of life as we know it - Rodriguez, Agustin Martin G (Archīum Ateneo, 2021)
Repentance and Rebirth is an exploration of the roots of our ecological crisis. Using a philosophical lens influenced by the metaphysics of play, discourse theory, the epistemology of a multiverse of rationalities, and an ecology of infinite responsibility, the author engages the various other disciplines from the science and the social sciences to understand why humans are destroying their own home. He examines the seemingly irrational and certainly self-destructive behavior from various perspectives in order to understand how we can repent the way we have realized ourselves in order to reimagine the possibilities of a more humane civilization. He believes that this end of life as we know it is offering an opportunity for human beings to rethink the destructive civilizations we have built.